2005
DOI: 10.1109/tbme.2005.851493
|View full text |Cite
|
Sign up to set email alerts
|

Image Overlay Guidance for Needle Insertion in CT Scanner

Abstract: Abstract-We present an image overlay system to aid needle insertion procedures in CT scanners. The device consists of a display and a semitransparent mirror that is mounted on the gantry. Looking at the patient through the mirror, the CT image appears to be floating inside the patient with correct size and position, thereby providing the physician with two-dimensional "X-ray vision" to guide needle insertions. The physician inserts the needle following the optimal path identified in the CT image rendered on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 19 publications
1
55
0
2
Order By: Relevance
“…Alternatively, AR windows have been explored for surgical guidance. Fichtinger et al [8] presented a medical image overlay system with a semi-transparent mirror that enabled surgeons to view overlaid 2D CT images that were reflected from a monitor. Mercier-Ganady et al [9] presented a system for viewing brain activity using augmented reality.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, AR windows have been explored for surgical guidance. Fichtinger et al [8] presented a medical image overlay system with a semi-transparent mirror that enabled surgeons to view overlaid 2D CT images that were reflected from a monitor. Mercier-Ganady et al [9] presented a system for viewing brain activity using augmented reality.…”
Section: Introductionmentioning
confidence: 99%
“…We showed on a static abdominal phantom that the targeting accuracy was about 2.5 mm. Obviously, the patient is not static, yet we believe like others [7,16,6,18] that pseudo-static conditions can be provided using a respiratory gating technique, i.e. the preoperative CT and the computer guidance are realized at the same point of the breathing cycle (generally expiration).…”
Section: Related Workmentioning
confidence: 95%
“…Fichtinger et al recently developed a system for conventional CT-scanner to assist needle placement [16,17]. It displays in the practitioner field of view one axial CT slice acquired intra-operatively, thereby providing a 2D internal view of the patient.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, specific 3D monitors generate a realistic three dimensional view for a predefined position of the observer. Further devices, like see-through mirrors [33], or projector based systems, which project images onto surfaces [74], have been developed for non endoscopic surgery. However, Herron et al found no significant advantage in comparison to conventional monitoring in a clinical evaluation of 3D visualization devices [46].…”
Section: Organ Shift and Tissue Deformationmentioning
confidence: 99%